2009
DOI: 10.1007/s11524-009-9353-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Intensive Volunteering to Promote the Health of Older Adults in Fair Health

Abstract: Volunteer service opportunities for older adults may soon be expanded. Although volunteering is thought to provide health benefits for healthier older adults, it is not known whether older adults in less than very good health are suitable candidates for high-intensity volunteering and can derive health benefits. This manuscript presents a prospective analysis of 174 older adult volunteers serving in Experience Corps Baltimore®, a high-intensity senior volunteer program in Baltimore, Maryland. Volunteers served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Volunteering has been associated with improved self-rated health, physical functioning, and quality of life as well as a decreased likelihood of functional dependency/disability and depression (Barron et al, 2009). For older gay men, the onset of the AIDS pandemic necessitated the need to take on greater roles in organizing and community activism (Institute of Medicine, 2011).…”
Section: Civic Engagementmentioning
confidence: 99%
“…Volunteering has been associated with improved self-rated health, physical functioning, and quality of life as well as a decreased likelihood of functional dependency/disability and depression (Barron et al, 2009). For older gay men, the onset of the AIDS pandemic necessitated the need to take on greater roles in organizing and community activism (Institute of Medicine, 2011).…”
Section: Civic Engagementmentioning
confidence: 99%
“…However, another study of women found that African American caregivers had less stress than White caregivers and experienced more benefits (Haley et al, 2004). Volunteering may positively affect the well-being of older adults (B. Cornwell et al, 2008), including African Americans (Barron et al, 2009;MorrowHowell, Hinterlong, Rozario, & Tang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Harris and Thoresen (2005) similarly found that volunteering is associated with a reduced risk of mortality. More recently, findings from several studies of Experience Corps volunteer programs suggest that high-intensity volunteering is associated with improved physical and mental health (Barron, Tan, Yu, Song, McGill, & Fried, 2009;Hong & Morrow-Howell, 2010).…”
Section: Volunteerismmentioning
confidence: 99%